Safety and Immunogenicity of a Meningococcal Quadrivalent Conjugate Vaccine in Five- to Eight-Year-Old Saudi Arabian Children Previously Vaccinated with Two Doses of a Meningococcal Quadrivalent Polysaccharide Vaccine - Khalil, Mohamed (American Society for Microbiology, 2012)
Saudi Arabian children respond poorly to 2 doses of meningococcal quadrivalent polysaccharide vaccine (MPSV4) when given before 2 years of age. This study examined whether such children were able to respond to 1 dose of quadrivalent meningococcal diphtheria toxoid conjugate vaccine (MCV4) when they were older. Saudi Arabian children 5 to 8 years of age who had previously been vaccinated with 2 doses of MPSV4 when they were under 2 years of age (termed the prior-MPSV4 group) were enrolled in a controlled, open-label, multicenter study. In the prior-MPSV4 group, children (n = 153) received 1 dose of MCV4, as did a group of age-matched meningococcal vaccine-naïve children (n = 85). Blood samples collected prevaccination and 28 days postvaccination were measured for serogroup-specific serum bactericidal antibody (SBA) levels in the presence of baby rabbit complement (rSBA) and for IgG antibody levels. Vaccine tolerability and safety were also evaluated. For all of the measured serogroups (A, C, Y, and W-135), the meningococcal vaccine-naïve participants achieved higher postvaccination rSBA geometric mean titers (GMTs) than did those in the prior-MPSV4 group. This was statistically significant for serogroup C (512 versus 167). Percentages of participants with postvaccination titers of ≥8 and with ≥4-fold increases in prevaccination to postvaccination titers appeared to be quite similar in the 2 groups. No worrisome safety signals were detected. MCV4 induced robust immune responses and was well tolerated in Saudi Arabian children who previously received 2 doses of MPSV4 as well as in those who were previously meningococcal vaccine naïve.